2018
DOI: 10.1016/j.bcp.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Sulfation of catecholamines and serotonin by SULT1A3 allozymes

Abstract: Previous studies have demonstrated the involvement of sulfoconjugation in the metabolism of catecholamines and serotonin. The current study aimed to clarify the effects of single nucleotide polymorphisms (SNPs) of human SULT1A3 and SULT1A4 genes on the enzymatic characteristics of the sulfation of dopamine, epinephrine, norepinephrine and serotonin by SULT1A3 allozymes. Following a comprehensive search of different SULT1A3 and SULT1A4 genotypes, twelve non-synonymous (missense) coding SNPs (cSNPs) of SULT1A3/S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…For example, SULT1A1 is involved in the biotransformation of acetaminophen, minoxidil, 4-hydroxytamoxifen, oxymorphone, nalbuphine, nalorphine, naltrexone, isoflavones, estradiol, and iodothyronines (Coughtrie et al, 1994;Nishiyama et al, 2002;Nowell and Falany, 2006;Kurogi et al, 2014;Marto et al, 2017). Likewise, SULT1A3 is known to metabolize catecholamines, serotonin, salbutamol, ritodrine, and troglitazone (Eisenhofer et al, 1999;Honma et al, 2002;Hui and Liu, 2015;Bairam et al, 2018); SULT1B1 plays a role in elimination of iodothyronines, thyroxine, and 1-naphthol (Fujita et al, 1997;Wang et al, 1998;Gamage et al, 2006); SULT1E1 metabolizes raloxifene and estrogens (Falany et al, 1995;Schrag et al, 2004Schrag et al, , 2006Cubitt et al, 2011); and SULT2A1 assists in metabolism of ciprofloxacin, desipramine, metoclopramide, dehydroepiandrosterone (DHEA), several bile acids, and 25-hydroxyvitamin D 3 (Falany et al, 1994;Meloche et al, 2002Meloche et al, , 2004Cook et al, 2009;Nakamura et al, 2009;Senggunprai et al, 2009;Huang et al, 2010;Wong et al, 2018). Because several of these substrates are s This article has supplemental material available at dmd.aspetjournals.org.…”
Section: Introductionmentioning
confidence: 99%
“…For example, SULT1A1 is involved in the biotransformation of acetaminophen, minoxidil, 4-hydroxytamoxifen, oxymorphone, nalbuphine, nalorphine, naltrexone, isoflavones, estradiol, and iodothyronines (Coughtrie et al, 1994;Nishiyama et al, 2002;Nowell and Falany, 2006;Kurogi et al, 2014;Marto et al, 2017). Likewise, SULT1A3 is known to metabolize catecholamines, serotonin, salbutamol, ritodrine, and troglitazone (Eisenhofer et al, 1999;Honma et al, 2002;Hui and Liu, 2015;Bairam et al, 2018); SULT1B1 plays a role in elimination of iodothyronines, thyroxine, and 1-naphthol (Fujita et al, 1997;Wang et al, 1998;Gamage et al, 2006); SULT1E1 metabolizes raloxifene and estrogens (Falany et al, 1995;Schrag et al, 2004Schrag et al, , 2006Cubitt et al, 2011); and SULT2A1 assists in metabolism of ciprofloxacin, desipramine, metoclopramide, dehydroepiandrosterone (DHEA), several bile acids, and 25-hydroxyvitamin D 3 (Falany et al, 1994;Meloche et al, 2002Meloche et al, , 2004Cook et al, 2009;Nakamura et al, 2009;Senggunprai et al, 2009;Huang et al, 2010;Wong et al, 2018). Because several of these substrates are s This article has supplemental material available at dmd.aspetjournals.org.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that the gene coding for SULT1A3 had undergone duplication during the evolutionary process generating two genes, designated SULT1A3 and SULT1A4, that encode identical protein products, collectively called SULT1A3 [18]. We recently employed site-directed mutagenesis in conjunction with bacterial expression and affinity purification to prepare twelve distinct SULT1A3 allozymes [21]. In this study, the twelve SULT1A3 allozymes, in comparison with the wild-type enzyme, were investigated for their sulfating activity toward phenylephrine and salbutamol.…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type and SULT1A3 allozymes were generated, expressed, and purified to greater than 95% homogeneity as previously reported [21].…”
Section: Preparation Of Wild-type and Sult1a3 Allozymesmentioning
confidence: 99%
“…Recombinant hSULTs (SULT1A1, SULT1A2, SULT1A3, SULT1B1, SULT1C2 SULT1C3, SULT1C4, SULT1E1, SULT2A1, SULT2B1a, SULT2B1b, SULT4A1, and SULT6B1), expressed using pGEX-2TK or pET23c prokaryotic expression system, were prepared as described previously ( Pai et al , 2002 ; Sakakibara et al , 2002 ; Suiko et al , 2000 ). The sulfating activity of purified recombinant hSULTs toward TMP-OH was assayed based on a previously established procedure ( Bairam et al , 2018 ), with radioactive PAP[ 35 S] as the sulfate donor. The assay mixture, following a 15 min reaction at 37°C, was separated by TLC and analyzed for [ 35 S]sulfated TMP-OH.…”
Section: Methodsmentioning
confidence: 99%